PENERAPAN MODEL PBL BERBANTUAN MEDIA WORDWALL UNTUK MENINGKATKAN HASIL BELAJAR MATEMATIKA SISWA - Laene, Riska R.; Bito, Nursiya; Takaendengan, Bertu Rianto (JURNAL MathEdu (Mathematic Education Journal), 2025)
This study aims to improve students' mathematics learning outcomes through the application of problembased learning models assisted by wordwall media on the material of comparison of values and inversecomparison of values. This study is a classroom action research conducted on 26 students of class VII-Cat SMP Negeri 1 Suwawa as research subjects. The study was conducted in two cycles by following thestages of planning, implementation of actions, observation and reflection. Data collection techniques werecarried out through observation sheets of teacher and student activities, as well as learning outcome tests.The results of the study showed a significant increase in students' mathematics learning outcomes throughProblem Based Learning assisted by wordwall media. This was obtained after the implementation of furtheractions to improve the teaching and learning process in cycle II. The results showed that observations ofall teacher activities in managing learning obtained at least good and very good aspects, observations ofall student activities obtained at least good and very good aspects, and students' mathematics learningoutcomes also increased by 65.4% to 88.46% of students who achieved the minimum completeness criteriaon the material of comparison of values and inverse comparison of values.